2015
DOI: 10.1007/s10488-015-0669-2
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Evaluation of a Weight Loss Intervention Program for People with Serious Mental Illnesses Taking Antipsychotic Medications

Abstract: Individuals with serious mental illnesses suffer from obesity and cardiometabolic diseases at high rates, and antipsychotic medications exacerbate these conditions. While studies have shown weight loss and lifestyle interventions can be effective in this population, few have assessed intervention cost-effectiveness. We present results from a 12-month randomized controlled trial that reduced weight, fasting glucose, and medical hospitalizations in intervention participants. Costs per participant ranged from $4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…These reductions are consistent with recent findings showing reduced hospitalizations among lifestyle intervention participants with diabetes and findings of sustained cardiovascular risk reduction among people with serious mental illnesses who received health coaching and a fitness club membership . In a cost‐effectiveness analysis conducted for this study, we estimated that reduced hospitalization costs would save ∼$137,500/year in each of the 2 years studied . Furthermore, diabetes prevention studies have consistently shown that lifestyle interventions reduce diabetes risk long after the trials have ended .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These reductions are consistent with recent findings showing reduced hospitalizations among lifestyle intervention participants with diabetes and findings of sustained cardiovascular risk reduction among people with serious mental illnesses who received health coaching and a fitness club membership . In a cost‐effectiveness analysis conducted for this study, we estimated that reduced hospitalization costs would save ∼$137,500/year in each of the 2 years studied . Furthermore, diabetes prevention studies have consistently shown that lifestyle interventions reduce diabetes risk long after the trials have ended .…”
Section: Discussionsupporting
confidence: 90%
“…( 14 ) In a cost-effectiveness analysis conducted for this study, we estimated that reduced hospitalization costs would save approximately $137,500/year in each of the two years studied. ( 34 ) Furthermore, diabetes prevention studies have consistently shown that lifestyle interventions reduce diabetes risk long after the trials have ended. ( 35 , 36 ) The steady decreases in fasting insulin levels found in this trial suggest that improved insulin sensitivity may help explain the long-term benefits of such lifestyle modification.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a severe mental illness (SMI), such as schizophrenia or bipolar disorders, have a shortened life targeting diet and physical activity in SMI patients visiting community mental health (MH) centers improved weight and fasting glucose levels after 12 months of intervention (6). Costs ranged from $4,365 to $5,687 (€3,501 to €5,461 using a 2014 Purchasing Power Parity (PPP) rate [7] of 0.802) (8). Costs per kilogram weight reduction were estimated from $1,623 to $2,114 (€1,302 to €1,695).…”
Section: Introductionmentioning
confidence: 99%
“…For example, across the review, when WMPs were compared with no treatment, they were more likely to be reported as cost-effective or dominant. 297,299,302…”
Section: Selection Of Controls Consideredmentioning
confidence: 99%
“…In summary, there was mixed evidence of remotely delivered (four studies) 142,296,300,301 and group-delivered (one study) 294 interventions being cost-effective. Most of the WMPs (13 studies) 128,142,149,163,[295][296][297][298][299][301][302][303][304] were found to be cost-effective; however, adding a meal replacement was not. A VLCD was found to be cost-effective in one study.…”
Section: Evaluations Of Remote Delivery Of Programmesmentioning
confidence: 99%